Peran Komunikasi Pemasaran dalam Penerapan Strategi Marketing Mix 7P pada Usaha Rental Alat Berat - Gusti Agung Ayu Made Listya Mahadewi; Ni Putu Intan Permatasari (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the role of marketing communication in the implementation of the 7P marketing mix strategy at the heavy equipment rental business CV. Dana Karya. Effective marketing communication is considered crucial in building customer loyalty, enhancing service quality, and strengthening the company’s position in a competitive market. The research used a qualitative approach, collecting data through in-depth interviews with 7 informants, including 2 primary informants and 5 supporting informants, as well as direct observation of the company’s operations. The analysis was conducted by linking field findings with the theory of Integrated Marketing Communication (IMC) and the 7P marketing mix concept, covering Product, Price, Place, Promotion, People, Process, and Physical Evidence. The results show that personal communication through WhatsApp, telephone, and direct interaction (Personal Selling) is the most effective channel for building long-term customer relationships, while Word of Mouth (WOM) serves as a natural promotion that enhances the company’s credibility. The application of the 7P marketing mix strategy supports service quality, where People, Process, and Physical Evidence significantly contribute to customer satisfaction. In addition, flexible pricing and the excellent condition of heavy equipment units serve as key differentiators compared to competitors. The study concludes that integrating marketing communication with the 7P marketing mix consistently can increase customer loyalty, service satisfaction, and business sustainability of CV. Dana Karya, with recommendations to strengthen digital promotion and develop a customer relationship management (CRM) program to expand market reach and retain loyal customers.